Portfolio choice and health status - Rosen, Harvey S; Wu, Stephen (Journal of Financial Economics, 2004)
This paper analyzes the role health status plays in household portfolio decisions using data from the Health and Retirement Study. The results indicate that health is a significant predictor of both the probability of owning different types of financial assets and the share of financial wealth held in each asset category. Households in poor health are less likely to hold risky financial assets, other things (including the level of total wealth) being the same. Poor health is associated with a smaller share of financial wealth held in risky assets and a larger share in safe assets. We find no evidence that the relationship between health status and portfolio allocation is driven by “third variables” that simultaneously affect health and financial decisions. Further, the relationship between health status and portfolio choice does not appear to operate through the effect of poor health on individuals’ attitudes toward risk, their planning horizons, or their health insurance status.